Mao's Images Artists and China's 1949 transition - Geng, Yan (Springer Fachmedien Wiesbaden, 2018)
In this book, Yan Geng examines Mao's image from the perspective of its producers, focusing on four artists, chosen for both the diverse media they worked in and their diverse backgrounds. The book suggests an alternative perspective on the making of propaganda not only as a politically themed representation but also as an expression of artists' subjectivities and their roles as pivotal agents in the transition of modern Chinese art history. Mao's Image: Artists and China's 1949 Transition demonstrates how artists portrayed Mao as the nation's leader during the early People's Republic and what such images reveal about Chinese artists' experience during the Communist takeover of the country. Contents • Image of political leader • Art media and propaganda production • Artists and politics Target Groups • Lectures and students of art, art history, and Asian studies • Researchers of modern Chinese art history The Author Yan Geng is currently an assistant professor of Asian art history at the University of Connecticut, USA. She completed her Ph.D. study in East Asian art history at Heidelberg University in Germany in 2012 and received fellowships from Haus der Kunst in Munich and the Morphomata Center for Advanced Studies in the Humanities at the University of Cologne.